The influence of normative whiteness in the South African private sector - Keene-Young, Bronwyn (Graduate School of Business (GSB), 2025)
Thirty years into democracy and notwithstanding the requirements of the Employment Equity Act (Act 55 of 1998), the South African private sector remains largely under the control of White executives, while Black African people constitute less than 20% of senior and top management (Commission for Employment Equity, 2023). Academic research (Myeza & April, 2021) as well as frequent anecdotal reports in mass and social media, indicate that Black professionals continue to experience racism in the private sector workplace, although this racism is often covert in nature and thus escapes the everyday understanding of the term. Studies by scholars of covert racism have established how normative Whiteness in society has operated to exclude or reduce the socio-economic prospects of Black people (Sue, 2010), but is rendered invisible through the establishment of ‘colour-blind' norms (Bonilla-Silva, 2018). However, there has been limited organisational research into how normative Whiteness, by maintaining an appearance of professional neutrality, perpetuates racism in the workplace (Nkomo, 1992, 2021). In addition, few studies on racism in organisations include the testimony of White executives as the primary data source. In this thesis I attempt to address this gap in the literature by using hermeneutic phenomenology within a critical theory framework to analyse how 35 White male and female executives at senior and top management level perceive: (i) Black professionals and their lived experiences and (ii) themselves and other White professionals; in the context of the employment equity imperatives of the South African private sector. As a White South African woman with over 15 years of experience in executive management, I include a self-reflexive approach both in the conducting of the interviews with White executives, as well as in the phenomenological analysis of the interview data. The significance of my research is that it shifts the study of racism to the locus of workplace power- White executives - and assesses how the normalisation of covert racism and Whiteness influences the perpetuation of organisational discrimination against Black professionals. My research shows that, notwithstanding ostensible support for the idea of employment equity, White executives' perceptions of Black people are shaped by stereotypes which perpetuate covert racism and the marginalisation of Black (particularly Black African) professionals. Concomitantly, White executives unknowingly establish Whiteness as a neutral standard for professional advancement and success in the South African private sector workplace.